Excited state entanglement on a two-electron system near the ionization threshold - Osenda, Omar (2008)
We have investigated the critical properties of the lowest-energy triplet state of the spherical helium atom. Using finite-size scaling methods we calculate critical charge and critical exponents for both the energy and the von Neumann entropy near the ionization threshold. We show that the scaling properties of the energy and the von Neumann entropy for this excited state are qualitatively different from those obtained for the ground state. These scaling properties are quantified in terms of critical exponents; therefore, the analysis is applicable to other few-fermion systems.